Hunting a 'good life': young lifestyle migrants in Finnish Lapland - Adams Ria-Maria (Polar Geography, 2023)
This article focuses on young lifestyle migrants in Arctic Finland, individuals who can be described as active agents of their own fate in having made a conscious choice to move to a place they consider worth living in. Drawing on long-term ethnographic research, the study brings to light newcomers’ motivations for migrating to a geographically remote area and discusses structural conditions that support the process of moving to Finnish Lapland. The search for personal wellbeing and a desire to construct “authentic” lifestyles in rural environments emerged as driving factors for young people who consider moving to the Arctic. While access to nature and nature-based leisure activities proved to be the most attractive feature of the region, opportunities to work in the tourism industry, well-connected transport infrastructures and educational opportunities also figured significantly in the migrants’ decisions. Of particular interest is the range of ways in which young migrants construct their lives, lives that run counter to the predominant narrative emphasizing the hardships of integration and adjustment as an immigrant. Among other means, social media channels play a pivotal role as a platform promoting their lifestyle. In engaging regularly with young people who have moved to the Arctic, where they pursue their chosen lifestyle in a harsh climate with high living costs, the research challenges the prevailing argument in the lifestyle migration debate whereby middle-class people move to places with lower living costs and sunny climates.